Policy as practice : toward a comparative sociocultural analysis of educational policy - Sutton, Margaret; Levinson, Bradley A., 1963- (Sociocultural studies in educational policy formation and appropriation ;, 2001)
This volume brings together scholars working on ethnographic policy studies to debate and provisionally chart the methodological and theoretical parameters of such a project. It is divided into three sections on theory, methods, and experiences, and features field experiences and case studies.